Impact of Minimal Processing on the Quality of the Sweet Celebration Grape Cultivar - Pereira, Bruna R.; Soares, Antonio G.; Barboza, Henriqueta T.G.; Coneglian, Regina C.C.; da Silva Vasconcellos, Marco A.; de Oliveira Fonseca, Marcos J. (Current Nutrition & Food Science, 2019)
Background: Nowadays, the producers have great interest on the apirenic grapes cultivars due to acceptance by all markets, besides the adding value to the product. The aim of this study was to evaluate the quality of minimally processed seedless grapes of the Sweet Celebration cultivar using three different solutions for the final wash of the berries and the removal or not of the peduncle were evaluated during twelve days stored at 8°C. Methods: The ‘Sweet Celebration’ cultivar grapes were washed and selected. Then they were submitted to a pre-washing step in chlorine solution. The berries with and without peduncle were submitted to a final wash using three different solutions: potable water, sodium metabisulfite and chlorine dissolved in water at 4±1°C. The evaluations of the minimally processed grapes were performed at zero, three, six, nine and twelve days of storage. Results: The firmness of the fruit was not affected by the solutions applied in the final wash. In general, berries without peduncle had higher cumulative weight loss, when compared to berries with peduncle, except for the sodium metabisulfite solution samples. The results suggest that water can be used for the final wash of the berries with peduncle as there was a lower weight loss of these fruits. The results with the other solutions applied and the sodium metabisulfite solution for the berries without peduncle were equivalent. Conclusion: The findings recommend use water as final wash solution to maintaining fruit quality of Sweet Celebration’ cultivar grapes when the peduncle is not removed.
Keywords: fresh-cut